Strategic Priorities and Challenges of Environmental Management in Kazakhstan - KARBETOVA, Zatira; KARBETOVA, Sholpan; OTYZBAYEVA, Karlygash; DARIBAYEVA, Adaskhan; DULATBEKOVA, Zhanar; TASTANBEKOVA, Karlygash (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The problem of sustainable ecological and economic development has been always relevant, and it is particularly relevant nowadays. Ecological safety of any state and improvement of living conditions today is largely related to the intensive socio-economic changes taking place in the country, as well as to the quantitative and qualitative changes in the environment caused by the impact of key industries. The purpose of this study is to develop recommendations for the organization and implementation of environmental management system through the industrial-innovative development, with the view of improving environmental protection in production and in other sectors of industry. Environmental problems are caused by pollution of the environment, air, etc. Under these circumstances, it is extremely important to solve ecological problems by conducting new studies in management, taking into account modern standards. This should be the paramount task in providing high quality of life and maintaining the ecological balance, which should be based on a comprehensive assessment of both production enterprises and companies engaged in other economic sectors, taking into account their versatility. Therefore, relevance of environmental tasks for both industrial enterprises and companies engaged in other economic sectors is steadily increasing. Research results justify the need to provide rational use of natural resources under current conditions, which should be combined with the maximum possible environmental preservation through technology improvement and minimizing harm to human health. The authors consider that improvement of environmental and economic situation demands the elaboration of ‘clean’ production.
Keywords: Environmental Management, Environmental Protection, sustainable development, economic modernization, modern technology